2018
DOI: 10.12659/msm.908381
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin Inhibites Migration and Invasion of Thyroid Cancer Cells by Downregulating DNMT1

Abstract: BackgroundShikonin is a component of Chinese herbal medicine. The aim of this study was to investigate the effects of shikonin on cell migration of papillary thyroid cancer cells of the TPC-1 cell line in vitro and expression levels of the phosphate and tensin homolog deleted on chromosome 10 (PTEN) and DNA methyltransferase 1 (DNMT1) genes.Material/MethodsThe Cell Counting Kit-8 (CCK-8) assay was performed to evaluate the proliferation of TPC-1 papillary thyroid cancer cells, and the normal thyroid cells, HTo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 42 publications
(40 reference statements)
1
14
0
2
Order By: Relevance
“…Wang et al ( 38 ) reported that shikonin inhibited the proliferation and promoted apoptosis of breast cancer cells. The results of the present study demonstrated that shikonin could inhibit proliferation, migration and invasion, and increase the apoptosis of A549 cells in a dose-dependent manner, which were consistent with the findings of previous studies ( 36 38 ). However, the results of the present study showed a lower apoptosis rate, which is different to the results obtained in the aforementioned studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Wang et al ( 38 ) reported that shikonin inhibited the proliferation and promoted apoptosis of breast cancer cells. The results of the present study demonstrated that shikonin could inhibit proliferation, migration and invasion, and increase the apoptosis of A549 cells in a dose-dependent manner, which were consistent with the findings of previous studies ( 36 38 ). However, the results of the present study showed a lower apoptosis rate, which is different to the results obtained in the aforementioned studies.…”
Section: Discussionsupporting
confidence: 93%
“…For example, a previous study reported that shikonin reduced the tumor diameter by 25% and increased the 1-year survival rate by 47.3% in patients with lung cancer ( 35 ). In addition, Zhang et al ( 36 ) demonstrated that shikonin inhibited the migration and invasion of thyroid cancer cells. Guo et al ( 37 ) also found that shikonin inhibited cell proliferation and induced apoptosis in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms underlying the anti-cancer activity of Shikonin seemed to be complicated and may depend on the cellular context (Wang et al, 2019). So far, the reported cellular targets of Shikonin include the pyruvate kinase isoenzyme M2 (PKM2) (Chen et al, 2011;Lu et al, 2018;Tang et al, 2018b), the MAPK pathway (Mao et al, 2008;Zhao et al, 2015;Shan et al, 2017), HIF1a (Li et al, 2017;Han et al, 2018;Tang et al, 2018b), JNK (Zhai et al, 2017;Lin et al, 2018), PI3K/AKT (Zhang et al, 2015;Zhou et al, 2017;Ni et al, 2018;Tang et al, 2018b), STAT3 (Qiu et al, 2017;Tang et al, 2018a), p16INK4A and p73 (Jang et al, 2015), and PTEN (Nigorikawa et al, 2006;Chen et al, 2018;Zhang et al, 2018). These findings, at one hand, demonstrate that Shikonin can regulate various biological processes (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that DNMT1 is an essential methyltransferase for the maintenance of DNA methylation. Previous evidence has shown that DNMT1 is overexpressed in breast cancer [41], thyroid cancer cells [42], and pancreatic cancer [43]. Furthermore, high DNMT1 expression is signi cantly associated with a poor prognosis [44,45].…”
Section: Discussionmentioning
confidence: 98%